Nutritional Quality of a Mixture of Indigofera sp. Leaves and Banana Steams Fermented Using Ma-11 Inoculant at Different Doses - Yunita Purnamasari; Ali Mursyid Wahyu Mulyono; Muhammad Husein (Jurnal Biologi Tropis, 2026)
Feed availability is one of the main constraints in livestock production, especially in tropical regions where supply is highly influenced by seasonal changes. Banana stems have potential as livestock feed due to their abundant availability; however, they contain low protein and high crude fiber, which requires processing to improve their nutritional quality. One of the methods that can be applied is fermentation using a bioactivator. This study aimed to evaluate the effect of different doses of Microbacter Alfaafa-11 (MA-11) inoculant on the nutritional quality of fermented banana stem and Indigofera sp. leaves. The study utilized a Completely Randomized Design (CRD) featuring three dose levels (0%; 0.05%; and 0.1%) and included four replicates over a period of 12 days of anaerobic fermentation. The measured variables were crude protein, crude fiber, and the weight of dry matter biomass. The data were examined using analysis of variance (ANOVA), followed by Duncan’s Multiple Range Test at a significance threshold of 5%. The findings indicated that the addition of MA-11 notably raised the crude protein level (P<0.05), with the highest value recorded at the 0.1% dose; however, it did not significantly affect (P>0.05) the crude fiber or the dry matter biomass weight. These findings indicate that MA-11 is more effective in improving protein content than in reducing crude fiber or modifying dry matter biomass weight.